1991
DOI: 10.1007/bf00016086
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of a wheat (Triticum aestivum L.) cDNA clone encoding the waxy protein

Abstract: The waxy mutation in maize is characterised by the complete loss of amylase in the starch fraction of the kernel [1,2,3]. In addition, there is a significant reduction in the amount of granule-bound starch synthase activity in the mutant [2] which correlates with the absence of a protein of 60 kDa, which in wild-type kernels is the most abundant protein associated with starch granules [4,5]. For this reason, it has been assumed that the 60 kDa waxy protein is the granule-bound starch synthase. Unequivocal evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 12 publications
0
36
0
2
Order By: Relevance
“…The dendrogram was generated using the PILEUP program (Devereux et al, 1984). The identities of the proteins are as follows: Agro GS, Agrobacterium glycogen synthase (Uttaro et al, 1990); Ecoli GS, €scherichia coli glycogen synthase (Kumar et al, 1986); Bsub GS, Bacillus subtilis glycogen synthase (Kiel et al, 1994); maize GBSSl (Klosgen et al, 1986); rice GBSSI (Okagaki, 1992); wheat GBSSI (Clark et al, 1991); barley GBSSI (Rohde et al, 1988); cassava GBSSI (Salehuzzaman et al, 1993); potato GBSSI (Visser et al, 1989); pea GBSSI (Dry et al, 1992); potato SSll (Edwards et al, 1995); pea SSll (Dry et al, 1992); rice SSS, rice soluble starch synthase (Baba et al, 1993); and potato SSlll (this study).…”
Section: Discussionmentioning
confidence: 99%
“…The dendrogram was generated using the PILEUP program (Devereux et al, 1984). The identities of the proteins are as follows: Agro GS, Agrobacterium glycogen synthase (Uttaro et al, 1990); Ecoli GS, €scherichia coli glycogen synthase (Kumar et al, 1986); Bsub GS, Bacillus subtilis glycogen synthase (Kiel et al, 1994); maize GBSSl (Klosgen et al, 1986); rice GBSSI (Okagaki, 1992); wheat GBSSI (Clark et al, 1991); barley GBSSI (Rohde et al, 1988); cassava GBSSI (Salehuzzaman et al, 1993); potato GBSSI (Visser et al, 1989); pea GBSSI (Dry et al, 1992); potato SSll (Edwards et al, 1995); pea SSll (Dry et al, 1992); rice SSS, rice soluble starch synthase (Baba et al, 1993); and potato SSlll (this study).…”
Section: Discussionmentioning
confidence: 99%
“…The accession numbers for the plants described in Figure 2B are as follows: barley (Hordeum vulgare), X07932 (Rohde et al, 1988); wheatI (Triticum aestivum), X57233 (Clark et al, 1991); maize (Zea mays), X03935 (Klosgen et al, 1986); sorghum (Sorghum bicolor), Q43134 (Y.C. Hsing, unpublished data); rice (Oryza sativa), X62134 (R.J. Okayaki, unpublished data); bean (Phaseolus vulgaris), AB029546 (N. Isono, K. Nozaki, H. Ito, H. Matsui, and M. Honma, un-…”
Section: Accession Numbersmentioning
confidence: 99%
“…It was originally identified in maize (Zea mays) kernels as the product of the waxy gene, and biochemical and genetic studies have shown that GBSS is responsible for the synthesis of the linear glycan (amylose) in starch (Nelson and Pan, 1995;Ball et al, 1998;Denyer et al 2001). Genes encoding the orthologous protein have been isolated from many different plant species, such as potato (Solanum tuberosum) (Dry et al, 1992;van der Steege et al, 1992), pea (Pisum sativum) (Dry et al, 1992), barley (Hordeum vulgare) (Rohde et al, 1988), wheat (Triticum aestivum) (Clark et al, 1991), snapdragon (Antirrhinum majus; MĂ©rida et al, 1999), and Arabidopsis (Tenorio et al, 2003). Although the analysis of mutants has demonstrated that GBSS is responsible for the synthesis of amylose in storage organs of diverse plants (Smith et al, 1997;Zeeman et al, 2010), no GBSS mutant involved in the accumulation of transitory starch has been thoroughly characterized to date.…”
Section: Introductionmentioning
confidence: 99%